Five on a secret trail - "Blyton, Enid" (Hodder Children's Books: London, 2001)
Julian, Dick, Anne, George and Timmy the dog find excitement and adventure wherever they go in Enid Blyton's most popular series. In book fifteen, the Famous Five go camping and pitch their tent near a ruined and seemingly abandoned cottage. When Anne hears strange noises at night the others don't believe her ... Until they see the ghostly lights. Is the cottage really haunted, or is there another, equally sinister, explanation?
Keywords: Action and adventure fiction